Healthcare resource utilization and costs in immunodeficient patients receiving subcutaneous Ig: Real-world evidence from France - Guillaume Lefèvre; Isabelle Borget; Cinira Lefèvre; Chahrazed Maherzi; Arnaud Nucit; Mouna Hennaoui; Aurélie Schmidt; Hannah Lennon; Benjamin Grenier; Florent Daydé; Nizar Mahlaoui (PLoS ONE, 2025)
Background Subcutaneous immunoglobulin (SCIg) replacement therapy is indicated for patients with hypogammaglobulinemia caused by primary (PID) and secondary immunodeficiencies (SID). Objective To compare healthcare resource utilization (HCRU) and related direct medical costs of patients in France treated with weekly conventional SCIg (cSCIg) vs monthly hyaluronidase-facilitated SCIg (fSCIg). Methods This retrospective study of Ig-naïve patients with PID or SID newly receiving a SCIg between 2016 and 2018, extracted from the French National Healthcare reimbursement database (SNDS), analyzed the SCIg-related HCRU and reimbursed costs generated from in-hospital (hospitalizations and SCIg doses) or at-home (nurse visits [NV] and pump provider visits [PPV], drug doses) SCIg administration. Results Overall, 2,012 patients (PID:534; SID:1,478) were analyzed. The follow-up duration varied between 7.5 and 8.7 months according to sub-groups. Compared with fSCIg-treated patients, monthly mean rates of NV and PPV were respectively 2.5 and 3.1 times higher in PID, and 1.6 and 3.1 times higher in SID cSCIg-treated patients. Monthly mean rates for SCIg administration-related hospitalizations were lower overall, while their costs were 1.6 and 1.8 times higher for cSCIg than fSCIg subgroups, in PIDs and SIDs respectively; these results are due to more frequent hospitalizations with fSCIg being mainly shorter, without stayover. Total HCRU costs from the French NHI’s perspective were estimated to be lower with fSCIg vs cSCIg, in PIDs and SIDs. Conclusion This study provides real-world evidence of SCIg administration in a large French population. Patients with PID or SID treated with fSCIg had fewer at-home HCRU and lower overall costs for in-hospital or at-home SCIg administration compared with cSCIg-treated patients.